PRODUCTIVITY ANALYSIS OF SPLIT STONE PRODUCTION USING OBJECTIVE MATRIX (OMAX) METHOD (A Case Study) - Indro Prakoso (Journal of Industrial Engineering and Halal Industries)
One of the building materials that has a high business prospect is split stone. Some building material management companies in one of their departments produce split stone, which in its production there are several types of products based on size to meet various consumer demands. In production, especially in the 2021 period, there will be fluctuating or uneven production levels, where in one month there will be high production, and in another period there will be a decrease in production. Based on this, this study aims to analyze the calculation of productivity to identify what factors cause the productivity of split stone production to fluctuate. This research was assisted by using the objective matrix (OMAX) and fault tree analysis (FTA) methods. the results of the productivity recapitulation found that the attendance data component obtained an average score of 2.3 which is the lowest average when compared to other components. therefore with these results, attendance is the strongest factor affecting fluctuating productivity.